To assess the potential use of tocolytic agents in a center with a low rate of preterm labour (< 34 weeks). (18th April 2012) - Walsh, N; Murphy, A; King, G; Mahony, R; Foley, M
Abstract : Background: Tocolytics are not used in this center. Purpose of study: To try and determine who might potentially benefit from tocolytics. Study design and Methods: This was a consecutive observational cohort study (Jan 2008 to Dec 2010) of singleton preterm births excluding inuterotransfers (IUT) with an independent secondary analysis (10 experts) of all PTL. Findings of the study: Among 27, 909 births, there were 283 preterm births (1%) of whom 75 (0.3%) delivered following PTL. Of these, 51 were excluded (27 had already received a complete course of antenatal corticosteroids, 18 were 4cm or greater on admission to the delivery ward and 4 were emergency deliveries (cord prolapse, placental abruption or fetal distress.). Of the remaining 24 patients (by almost unanimous agreement) 15 were not considered suitable for tocolytics because of spontaneous rupture of the membranes (n=6), antepartum haemorrhage (n=6) and suspected chorioamnionitis or fetal distress ( n=3). Nine case (0.03%) or 12% of PTL (9/75) were considered as potential candidates for tocolytics. Of these the diagnosis of labor was made correctly in 8 cases: 2 delivered with one hour remaining 6 labored for a mean of 6 hours and may have responded to tocolytics. Conclusions: The number of potential cases over a three year period is very small, but the diagnosis of labor within this group was so accurate that selective use of tocolytics might be considered while a randomised trial would be difficult with the numbers involved.